Reversible Electrochemical Insertion of Lithium in Fine Grained Polycrystalline Powders of SnO2 - S. D. Han; S. Y. Huang; G. Campet; S. H. Pulcinnelli; C. V. Santilli (Active and Passive Electronic Components)
Fine grained SnO2 powders have been obtained using an unconventional method. It deals with the well known polymerization method starting from the metallic halide SnCl4 with polyethylene oxide (PEO). With this method, SnO2 powders, which are free from water and hydroxyl group contaminations and possess small crystallite size (≈50 A∘), are obtained by appropriate pyrolysis of the polymer. Consequently, these powders show good ability to insert reversibly lithium ions in the Li/Li+/LixSnO2 cell. Indeed, by minimizing the size of the crystallites, the formation of defect-bonds is favored, particularly at the crystallite surface, acting as reversible (de)grafting sites of Li+. Finally, an easy-to-carry out method to determine the chemical diffusion coefficient of lithium has been proposed.